Intelligent Reflecting Surfaces for Enhanced NOMA-based Visible Light Communications - Abumarshoud, Hanaa; Selim, Bassant; Tatipamula, Mallik; Haas, Harald (IEEE International Conference on Communications (2003), 2022)
The emerging intelligent reflecting surface (IRS) technology introduces the potential of controlled light propagation in visible light communication (VLC) systems. This concept opens the door for new applications in which the channel itself can be altered to achieve specific key performance indicators. In this paper, for the first time in the open literature, we investigate the role that IRSs can play in enhancing the link reliability in VLC systems employing non-orthogonal multiple access (NOMA). We propose a framework for the joint optimisation of the NOMA and IRS parameters and show that it provides significant enhancements in link reliability. For example, the bit-error-rate of the NOMA user in the first decoding order is reduced to the order of 10 −6 using the proposed framework compared to an error floor of 10 −2 under fixed power allocation and fixed IRS reflection coefficients. The enhancement is even more pronounced when the VLC channel is subject to blockage and random device orientation.